Withdrawn : Observations of nutrient supply by mesoscale eddy stirring and diapycnal mixing in the oligotrophic North Atlantic - Spingys, Carl P.; Williams, Richard G.; Tuerena, Robyn E.; Garabato, Alberto Naveira; Vic, Clement; Forryan, Alexander; Sharples, Jonathan (Global Biogeochemical Cycles, 2021)
Sustaining biological export over the open ocean requires a compensating physical supply of nutrients to the euphotic zone. The relative importance of diapycnal mixing and isopycnal stirring by mesoscale eddies in providing this nutrient supply is explored using a field campaign in some of the most oligotrophic waters in the subtropical North Atlantic, using transects over and off the mid-Atlantic ridge. Eddy stirring rates are estimated, firstly, from the excess temperature variance dissipation relative to the turbulent kinetic energy dissipation and, secondly, using eddy statistics from satellite observations combined with 9-month-long mooring data. The vertical nutrient fluxes by diapycnal mixing and isopycnal mesoscale eddy stirring are assessed using nitrate measurements from observations or a climatology. The diapycnal transfer provides a nutrient supply within the euphotic zone, but induces a loss of nutrients within the upper thermocline. Eddy stirring augments, and is comparable to, the diapycnal transfer of nutrients within the summertime upper thermocline, while also acting to replenish nutrients within the deeper parts of the thermocline. The eddy supply of nitrate is relatively small in the centre of the subtropical gyre, reaching up to 0.06 mol N m−2yr−1, but is likely to be enhanced on the flanks of the gyre due to larger isopycnal slopes and lateral nitrate gradients. The nutrient supply to the euphotic zone is achieved via a multi-stage mechanism: a diapycnal transfer of nutrients by small-scale turbulence to the euphotic zone and an isopycnal stirring of nutrients by mesoscale eddies replenishing nutrients in the upper thermocline. Plain Language Summary Phytoplankton growth requires a supply of nutrients to the base of the euphotic zone, which is usually provided by a combination of vertical mixing or vertical upwelling of nutrients. However, in the oligotrophic waters of the central North Atlantic, it is unclear how the vertical supply of nutrients is sustained. Here we use field data to ...